حماية المستهلك الإلكتروني في ظل التشريعات الدولية - ستو, فاطمة الزهرة; جديدي, روضة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى تسليط الضوء على أهم الجهود والتشريعات الدولية لحماية المستهلك الإلكتروني من أهم المخاطر والجرائم التي يتعرض لها في ظل المعاملات الإلكترونية. حيث تركزت جهودهم بشكل خاص على وضع مدونات للسلوك المقبول والإيجابي الذي يجب أن تتحلى به الأطراف المتعاملة في هذا الفضاء من أجل تحقيق ممارسات شريفة، وعلى الجزائر أن تواكب هذه الدول رغم ما تعانيه من تأخر كبير في هذا النوع من المعاملات. وقد تم الاعتماد في هذه الدراسة على المنهج الوصفي والتحليلي لملائمته لطبيعة الموضوع، حيث توصلت إلى عدم وجود إطار قانوني قادر على ضمان حقوق المستهلك الإلكتروني وحمايته في ظل المعاملات الإلكترونية لكون العقد الإلكتروني يكون بين طرفين في دولتين مختلفتين ولكل دولة قانونها الخاص بها. This study aims to shed light on the most important international efforts and legislation to protect the electronic consumer from the most important risks and crimes that he is exposed to in light of electronic transactions. Their efforts focused in particular on developing codes of acceptable and positive behavior that the parties involved in this space must exhibit in order to achieve honorable practices, and Algeria must keep pace with these countries despite the great delay it suffers from in this type of transactions. In this study, the descriptive and analytical approach was relied on for its relevance to the nature of the subject, as it concluded that there is no legal framework capable of guaranteeing and protecting the rights of the electronic consumer in light of electronic transactions because the electronic contract is between two parties in two different countries, and each country has its own law
Electronic consumer protection under international legislation
مقال
Keywords: مستهلك إلكتروني، معاملات إلكترونية، عقد إلكتروني، تشريعات دولية.